Pengaruh SiMBA terhadap Efisiensi Operasional Pengelolaan Zakat: Studi Kasus BAZNAS Kabupaten Enrekang - Hasrianti Hasrianti; Marhani; Ismayanti; Alfian Ardi Syaputra (Department of Management Zakat and Waqf, 2024)
This study aims to analyze the utilization of the BAZNAS Information Management System (SiMBA) in zakat management efforts and to determine the application of SiMBA in optimizing zakat management at BAZNAS Enrekang Regency. This research seeks to provide a comprehensive understanding of how SiMBA is implemented and utilized in BAZNAS operations, as well as to examine the effectiveness of the system in enhancing the efficiency and effectiveness of zakat management in the region. This research uses a qualitative phenomenology approach, involving data reduction from interviews, observations, and documents for narrative analysis. The research is located at the BAZNAS Office of Enrekang Regency. Data collection techniques include observation, interviews, and documentation. Data validity is tested through credibility, transferability, dependability, and confirmability. Data analysis uses reduction, presentation, and conclusion drawing. The results showed that the use of SiMBA at BAZNAS Enrekang Regency has not been fully optimized due to several constraints in its implementation, such as incomplete muzakki data and the need for continuous application updates